THE STRATEGICMANAGEMENT OF LAKE TOBA DEVELOPMENT - Posma Sariguna Johnson Kennedy (S1 Accounting Department, Faculty of Economic, Universitas Pamulang., 2018)
To fulfill Sustainable Development Goals which is a document that become a reference in the framework of development in the world, one of the goals is the suistainable tourism issue for welfare. The government wants to make Lake Toba as one of the priority tourist destinations. Lake Toba with the beauty of the largest volcanic caldera in the world can invite demand for both domestic and foreign tourists. It is important to improve theenvironmental condition of the lake itself and how the infrastructure to reach the tourist destinations. The main purpose of this paper is to analyze the strategic management of Lake Toba development. The research method used is qualitative method. The government wants the best strategy with various implementations to prepare Lake Toba as a world tourism destination.